The Influence of Procurement Compliance in Public Procurement Performance: A Case of Bahi District Council, Tanzania - Sama, Hamisi Kileo; Mwalukasa, Boniface E. (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This paper aims to investigate the factors influencing procurement compliance in public procurement performance within the Bahi District Council in Tanzania. Design/methodology/approach: A descriptive research design was employed to gather data from 55 respondents through a closed-ended questionnaire. Findings: The study found that internal control systems, users’ knowledge, and ethics significantly affect procurement compliance at a significance level of p < 0.05. Practical implications: To enhance compliance with public procurement acts and regulations, policymakers are urged to create an enabling environment for the implementation of internal control systems, users’ knowledge, and ethical standards in public entities. Paper type: Empirical research.